A longitudinal study of the association between inattention, hyperactivity and impulsivity and children’s academic attainment at age 11 - Merrell, Christine; Sayal, Kapil; Tymms, Peter; Kasim, Adetayo (Elsevier, 2017)
Background: The link between inattention and hyperactivity/impulsivity and poor academic outcomes is well established. Children with mild difficulties can go unnoticed yet may be at risk of poor academic outcomes.